Assessing global climate change mitigation scenarios from a power system perspective using a novel multi-model framework. (April 2022) - Brinkerink, Maarten; Zakeri, Behnam; Huppmann, Daniel; Glynn, James; Ó Gallachóir, Brian; Deane, Paul
Abstract: There is a debate regarding the suitability of global integrated assessment models (IAMs) for long-term planning exercises of the global energy system. This study informs this debate from a power system perspective and proposes a methodological framework for soft-linking of global IAMs with detailed global power system models. With the proposed open-source framework, the scenario results from IAMs can be fed into a power system model to assess given scenarios with enhanced modelling resolution. Results from these simulations can be redirected to the IAM through iterative bi-directional soft-linking. A proof of concept application is presented by linking global IAM MESSAGEix-GLOBIOM with global power system model PLEXOS-World. Among others, the results suggest that the assumption of unconstrained electricity flows inside large regional copperplates without internal network constraints causes an overestimation of the potential of variable renewables within MESSAGEix-GLOBIOM. We propose areas for informed improvements in MESSAGEix-GLOBIOM and for IAMs in general. Highlights: We present a framework for linking global integrated assessment models (IAMs) with global power system models. Results from global IAMs can be assessed at high spatial, technological, and temporal model resolution. Standardized workflows allow for iterative application of the bi-directional model soft-link. Global IAM MESSAGEix-GLOBIOM has been linked to global power system model PLEXOS-World. Suggested model improvements have been identified and integrated for MESSAGEix-GLOBIOM.